Absolute beginner's guide to Microsoft Office OneNote 2003 - Cardoza, Patricia (Que, 2004)
OneNote offers the flexibility of a paper notebook and the power of digital note takingnote taking. Absolute Beginner's Guide to Microsoft Office OneNote 2003 covers all the features of the software to help users get up to speed quickly on this new note taking and management program. It begins by explaining what OneNote is and why a consumer would want to buy it. The book continues to show the reader how to type in his first note, use the pen, organize notes, draw pictures, add audio and much more. This title also highlights the benefits of using OneNote in a business or school environment.